The Oxford handbook of global modernisms - Eatough, Matt; Wollaeger, Mark A. (Oxford University Press, 2012)
The Oxford Handbook of Global Modernisms expands the scope of modernism beyond its traditional focus to explore the contributions of artists from regions like Spain, the Balkans, China, Japan, India, Vietnam, and Nigeria. Together, these essays offer the most comprehensive worldwide examination of modernist studies available. Topics covered include: Richard Wright and photographic modernism; poetry of the Caribbean; Chinese modernism and Lu Xun's Ah Q-The Real Story; Ben Okri and magical realism; aesthetic autonomy in Paris, Italy, Russia; Cuba's avant-gardes; geography of Hebrew and Yiddish modernism in Europe; Japanese modernism in works by Kitagawa Fuyuhiko and Yokomitsu Riichi; and South African cinema.